Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a) (x2-6xy+9y2):(3y-x)
= (x-3y)2:(3y-x)
=(3y-x)2:(3y-x)
= 3y-x
b) (8x3-1):(4x2+2x+1)
=[(2x)3-1]:(4x2+2x+1)
= (2x-1)(4x2+2x+1):(4x2+2x+1)
= 2x-1
c) (4x4-9):(2x2-3)
=(2x2-3)(2x2+3):(2x2-3)
=2x2+3
d) (8x3-27):(4x2+6x+9)
=(2x-3)(4x2+6x+9):(4x2+6x+9)
=2x-3
a: Ta có: \(x^2-6x+9-y^2\)
\(=\left(x-3\right)^2-y^2\)
\(=\left(x-y-3\right)\left(x+y-3\right)\)
b: Ta có: \(x^3+4x^2+4x\)
\(=x\left(x^2+4x+4\right)\)
\(=x\left(x+2\right)^2\)
c: Ta có: \(4xy-4x^2-y^2+9\)
\(=-\left(4x^2-4xy+y^2-9\right)\)
\(=-\left(2x-y-3\right)\left(2x-y+3\right)\)
a) \(4x^2+20x+25=\left(2x+5\right)^2\)
b) \(x^2-6x+9=\left(x-3\right)^2\)
c) \(4x^2+12x+9=\left(2x+3\right)^2\)
x2 +6xx+9=4x2-4x+1
<=>3x2-10x -8=0
<=>3x2-12x+2x-8 =0
<=>3x(x-4)+2(x-4)=0
<=>(3x+2)(x-4)=0
<=>x =-2/3 hoặc x=4
x2 +6xx+9=4x2-4x+1
<=>3x2-10x -8=0
<=>3x2-12x+2x-8 =0
<=>3x(x-4)+2(x-4)=0
<=>(3x+2)(x-4)=0
<=>x =-2/3 hoặc x=4
a: \(A=\dfrac{2\left(x+3\right)}{\left(x+3\right)\left(x-2\right)}=\dfrac{2}{x-2}\)
b: \(B=\dfrac{\left(x-3\right)\left(x+3\right)}{\left(x-3\right)^2}=\dfrac{x+3}{x-3}\)
c: \(C=\dfrac{\left(3x-4\right)\left(3x+4\right)}{x\left(3x-4\right)}=\dfrac{3x+4}{x}\)
d: \(D=\dfrac{\left(x+2\right)^2}{2\left(x+2\right)}=\dfrac{x+2}{2}\)
e: \(E=\dfrac{-x\left(x-2\right)}{\left(x-2\right)\left(x+2\right)}=\dfrac{-x}{x+2}\)
f: \(F=\dfrac{3\left(x^2+2x+4\right)}{\left(x-2\right)\left(x^2+2x+4\right)}=\dfrac{3}{x-2}\)
a) \(\frac{4x+3}{6x-4}+\frac{5x-9}{6x-4}\)
\(=\frac{4x+3+5x-9}{2\left(3x-2\right)}=\frac{9x-6}{2\left(3x-2\right)}\)
\(=\frac{3\left(3x-2\right)}{2\left(3x-2\right)}=\frac{3}{2}\)
b) \(\frac{2}{x-1}+\frac{3}{x+1}-\frac{4x-2}{x^2-1}\)
\(=\frac{2\left(x+1\right)+3\left(x-1\right)-4x+2}{\left(x-1\right)\left(x+1\right)}\)
\(=\frac{x+1}{\left(x-1\right)\left(x+1\right)}=\frac{1}{x-1}\)
a) \(\frac{4x+3}{6x-4}+\frac{5x-9}{6x-4}\)
\(=\frac{4x+3+5x-9}{6x-4}\)
\(=\frac{9x-6}{6x-4}\)
\(=\frac{3.\left(3x-2\right)}{2.\left(3x-2\right)}\)
\(=\frac{3}{2}.\)
b) \(\frac{2}{x-1}+\frac{3}{x+1}-\frac{4x-2}{x^2-1}\)
\(=\frac{2}{x-1}+\frac{3}{x+1}-\frac{4x-2}{\left(x-1\right).\left(x+1\right)}\)
\(=\frac{2.\left(x+1\right)}{\left(x-1\right).\left(x+1\right)}+\frac{3.\left(x-1\right)}{\left(x-1\right).\left(x+1\right)}-\frac{4x-2}{\left(x-1\right).\left(x+1\right)}\)
\(=\frac{2x+2}{\left(x-1\right).\left(x+1\right)}+\frac{3x-3}{\left(x-1\right).\left(x+1\right)}+\frac{-\left(4x-2\right)}{\left(x-1\right).\left(x+1\right)}\)
\(=\frac{2x+2+3x-3-4x+2}{\left(x-1\right).\left(x+1\right)}\)
\(=\frac{x+1}{\left(x-1\right).\left(x+1\right)}\)
\(=\frac{1}{x-1}.\)
Chúc bạn học tốt!
Bài giải
\(4x\left(2x^2-1\right)+27=\left(4x^2+6x+9\right)\left(2x+3\right)\)
\(8x^3-4x+27=8x^3+12x^2+18x+12x^2+18x+27\)
\(8x^3-4x+27=8x^3+24x^2+36x+27\)
\(8x^3-4x+27-8x^3-36x-27=24x^2\)
\(-40x=24x^2\)
\(\frac{3}{5}x^2=x\)
\(\frac{3}{5}x^2-x=0\)
\(x\left(\frac{3}{5}x-1\right)=0\)
\(\Rightarrow\left[{}\begin{matrix}x=0\\\frac{3}{5}x-1=0\end{matrix}\right.\Rightarrow\left[{}\begin{matrix}x=0\\\frac{3}{5}x=1\end{matrix}\right.\Rightarrow\left[{}\begin{matrix}x=0\\x=\frac{5}{3}\end{matrix}\right.\)
\(\Rightarrow\text{ }x\in\left\{0\text{ ; }\frac{5}{3}\right\}\)
Bài làm:
a) Ta có: \(C=4x^2+4x+1=\left(2x+1\right)^2\)
Tại x = 50 ta được: \(C=\left(2.50+1\right)^2=101^2=10201\)
b) Ta có: \(E=x^2-6x+9=\left(x-3\right)^2\)
Tại x = 93 ta được: \(E=\left(93-3\right)^2=90^2=8100\)
\(C=9+6x-4x^2\)
\(=-4\left(x^2-\frac{3}{2}x\right)+9\)
\(=-4\left(x^2-\frac{3}{2}x+\frac{9}{16}\right)+\frac{9}{4}+9\ge\frac{9}{4}+9\)